Medicinal Plants and Natural Products to Treat Obesity through Inhibiting Pancreatic Lipase: A Review (2020-2022) - Jamai, Khaoula; Daoudi, Nour E.; Elrherabi, Amal; Bnouham, Mohamed (Letters in Drug Design & Discovery, 2024)
Pancreatic lipase is an enzyme that catalyzes the hydrolysis of triglycerides to monoglycerides and free fatty acids which promote and accelerate their absorption by the intestine, thus leading to obesity. Drugs that have numerous side effects explain the beneficial medicinal effect of plants resulting from their Phyto molecules that exhibit strong anti-lipase activity. The present review reveals the medical treatment and consequently the associated side effects. It also represents an update of various medicinal plants and their metabolites that act as lipase inhibitors published between (2020-2022). We have discussed 93 species belonging to 48 different plant families and numerous bioactive molecules exerting this activity. We have compared 29 species for their anti-lipase potential. Fabaceae and Lamiaceae were the most dominant with 7 species, and the highest percentage (95%) for pancreatic lipase inhibitory activity was recorded by “Filipendula kmtaschatia” from Rosaceae family while “Piper betle” from Piperaceae family showed the lowest percentage (15.9%). The medical treatments with low dose effect were liraglutide saxenda (3mg/day), also flavonoids, in particular catechin derivatives, which were the most potent in terms of pancreatic lipase inhibitory activity with the lowest IC50s. This study summarized medical and natural treatments that are used to treat obesity through inhibiting pancreatic lipase and delaying fat assimilation in the intestines. So far, more studies are needed for the use of these as herbal medicine for obesity.
Keywords: Obesity